In situ Growth of Cu2O/CuO Nanosheets on Cu Coating Carbon Cloths as a Binder-Free Electrode for Asymmetric Supercapacitors - Xu, Lina; Li, Jiao; Sun, Haibin; Guo, Xue; Xu, Jiakun; Zhang, Hua; Zhang, Xiaojiao (Frontiers in Chemistry, 2019)
Cu2O/CuO nanosheets in-situ grown on Cu-Carbon cloths (Cu-CCs), namely Cu2O/CuO@Cu-CCs, are constructed by a simple strategy with electroless copper plating, chemical etching and thermal dehydration. The as-prepared material is directly used as binder-free electrodes for supercapacitors. CCs coated with Cu, as the current collector, can effectively promote the charge collection and electron transfer, while the hierarchical Cu2O/CuO nanosheets provide massive active sites for fast faradic reactions. The composite electrode exhibits high specific capacitance (1.71 F cm-2, equivalent to 835.2 F g-1, at the current density of 10 mA cm-2 (3.57 A g-1)). The asymmetric supercapacitor device using Cu2O/CuO@Cu-CCs as the positive electrode and activated carbon as the negative electrode, achieves a superior energy density up to 60.26 Wh kg-1 at a power density of 299.73 W kg-1 and an excellent long-term cycling stability (9.65% loss of its initial capacitance after 5000 cycles). The excellent electrochemical performance is mainly ascribed to the unique hierarchical structure of Cu2O/CuO@Cu-CCs, making it attractive as a potential electrode material for high performance supercapacitors.